Utilization of oil palm wastes in south western Nigeria (2003)
A survey involving the use of questionnaires and personal communication during field visits was undertaken in Ekiti, Ogun, Ondo, Osun and Oyo states of Nigeria to ascertain the level of utilization of the inedible portions of oil palm products often referred to as wastes. Items identified as wastes and their present uses include trunk for bridges and roof trusses; fronds and leaves for brooms, thatching of roofs and fences, staking of creeping and climbing plants, weavmg of baskets and cages and cordage materials; fruit bunches for black soap production; kernel shells for soil erosion control and furnace fuel; and mill effluents for sludge cake used as fuel, A substantial amount of these wastes are unutilized which has resulted in their constituting nuisance in plantations and mill sites. Incineration is the only disposal method employed to create space for other activities. It is recommended that the use of these wastes be popularized among urban dwellers to create market for them. Fruit harvesting and conversion of the trunk are tedious; hence the development of appropriate technology for improved efficiency required.